2020
DOI: 10.1038/s41467-020-14527-2
|View full text |Cite|
|
Sign up to set email alerts
|

Naturally-occurring cholesterol analogues in lipid nanoparticles induce polymorphic shape and enhance intracellular delivery of mRNA

Abstract: Endosomal sequestration of lipid-based nanoparticles (LNPs) remains a formidable barrier to delivery. Herein, structure-activity analysis of cholesterol analogues reveals that incorporation of C-24 alkyl phytosterols into LNPs (eLNPs) enhances gene transfection and the length of alkyl tail, flexibility of sterol ring and polarity due to-OH group is required to maintain high transfection. Cryo-TEM displays a polyhedral shape for eLNPs compared to spherical LNPs, while x-ray scattering shows little disparity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
300
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(310 citation statements)
references
References 72 publications
10
300
0
Order By: Relevance
“…Recently, we discovered a simple substitution of cholesterol to β-sitosterol within LNP formulations boosts intracellular delivery of mRNA 22,23 . We compared the enhanced LNP formulation (eLNP: containing β-sitosterol) with the conventional LNP (containing cholesterol) as the delivery vector for hsACE2 mRNA.…”
Section: Mainmentioning
confidence: 99%
“…Recently, we discovered a simple substitution of cholesterol to β-sitosterol within LNP formulations boosts intracellular delivery of mRNA 22,23 . We compared the enhanced LNP formulation (eLNP: containing β-sitosterol) with the conventional LNP (containing cholesterol) as the delivery vector for hsACE2 mRNA.…”
Section: Mainmentioning
confidence: 99%
“…The addition of cholesterol into the formulation has been shown to the enhance transfection efficiency of lipid-base nanoparticles, potentially by promoting membrane fusion and endosomal escape and, as expected, the percentage of cholesterol has a considerable influence on intracellular gene delivery (Pozzi et al, 2012). Patel et al reported that the inclusion of a naturally occurring cholesterol analogous (C-24 alkyl phytosterols) into lipid-based nanoformulations enhances mRNA delivery (Patel et al, 2020). In this regard, the length of the alkyl tail, the flexibility of sterol ring and the polarity associated with the hydroxyl group were found essential to maintain a high transfection efficiency.…”
Section: Helper Lipids and Stealth Lipidsmentioning
confidence: 85%
“…With a near atomic resolution (57), EM is an irreplaceable tool in studying the physio-chemical properties of NP and quantifying their voyage through the endo-lysosomal pathway (30,37,(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). EM can even detect a low number (few hundreds) of single nanoparticles escaping endosomal structures, and since it is a label-free method, it will localise and quantify NP generally untraceable by standard light microscopy methods.…”
Section: Electron Microscopy and Cryo-electron Microscopymentioning
confidence: 99%
“…Various papers study the endosomal escape of NP using several independent microscopic techniques (30,58,68,140,141). However, a correlative approach is more desirable, as it Up to date, the only CLEM approach used to quantitatively study endo-lysosomal tracking of NP has been developed by Han et al (74) (Fig.…”
Section: Correlative Imagingmentioning
confidence: 99%